2015
DOI: 10.1051/hydro/2015004
|View full text |Cite
|
Sign up to set email alerts
|

Fish population dynamic in the newly impounded Nam Theun 2 Reservoir (Lao PDR)

Abstract: -A fish population monitoring was carried out in the reservoir and tributaries of the hydropower project Nam Theun 2 (Lao PDR) at the end of the warm and dry seasons and at the end of the warm and wet seasons between 2008 and 2013. The study focused on three aquatic systems (river upstream, transition area, and reservoir) and different drowned habitats (dense/light forests and agricultural soils) associated or not with the presence of villages. The reservoir fish population was expected to follow three distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 33 publications
(41 reference statements)
3
22
0
Order By: Relevance
“…The rapid response of these riverine fishes corresponds with previous evidence from tropical systems (Agostinho et al, 2016, ; Cottet et al, ; Henderson, Ryder, & Kudhongania, 1; Williams, Winemiller, Taphorn, & Balbas, ) and fits the general expectation of Turgeon et al () with fish populations in this tropical reservoir peaking considerably faster (0.9–1.4 years) than temperate (4.1 years) and boreal (4.5 years) systems. Although the short fill time (4 months) was clearly an important factor, the quick ecological response was primarily a consequence of the higher productivity of warm‐water ecosystems (Brown, Gillooly, Allen, Savage, & West, ; Lowe‐McConnell ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The rapid response of these riverine fishes corresponds with previous evidence from tropical systems (Agostinho et al, 2016, ; Cottet et al, ; Henderson, Ryder, & Kudhongania, 1; Williams, Winemiller, Taphorn, & Balbas, ) and fits the general expectation of Turgeon et al () with fish populations in this tropical reservoir peaking considerably faster (0.9–1.4 years) than temperate (4.1 years) and boreal (4.5 years) systems. Although the short fill time (4 months) was clearly an important factor, the quick ecological response was primarily a consequence of the higher productivity of warm‐water ecosystems (Brown, Gillooly, Allen, Savage, & West, ; Lowe‐McConnell ).…”
Section: Discussionsupporting
confidence: 87%
“…The rapid response of these riverine fishes corresponds with previous evidence from tropical systems Cottet et al, 2015;Henderson, Ryder, & Kudhongania, 11973;Williams, Winemiller, Taphorn, & Balbas, 2011) fill time (4 months) was clearly an important factor, the quick ecological response was primarily a consequence of the higher productivity of warm-water ecosystems (Brown, Gillooly, Allen, Savage, & West, 2004;Lowe-McConnell 1987). The resultant TU parallels the response of floodplain ecosystems where seasonal inundation boosts fish populations (Agostinho, Gomes, Samuel, & Okada, 2004;Castello et al, 2015;Welcomme, 2001), inspiring the elaboration of DF as a strategy to further increase fisheries production (Sabo et al, 2017).…”
Section: Peak Timing and Durationsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with this logic, we found that the trophic non-equilibrium phase was on average longer in boreal reservoirs compared to temperate ones. Furthermore, indirect evidence from commercial and recreational fisheries landings and knowledge of tropical reservoirs suggest that the duration of the trophic surge can be relatively short (2-10 yr; Henderson et al 1973, Balon and Coche 1974, Williams et al 1998, Agostinho et al 1999, Hallwass et al 2012, Cottet et al 2015.…”
Section: Variation In the Trophic Surgementioning
confidence: 99%
“…From April 2012 to August 2016, fish were collected from different stations of the Nam Theun 2 reservoir (17°48′N; 105°6′E) during surface gillnet surveys (gill nets: 25 × 2 m; mesh size: 10,15,20,25,30,35,40,50,60 and 70 mm between knots) conducted on a monthly basis in two reservoir stations and a quarterly basis in three additional stations (NTPC, 2014). Main features of the Nam Theun 2 area are presented in detail in Descloux, Guedant, Phommachanh, and Luthi (2016), and map and fish sampling stations in Cottet, Descloux, Guédant, Cerdan, and Vigouroux (2016). To strengthen the dataset for larger and smaller individuals, additional data were collected.…”
Section: Methodsmentioning
confidence: 99%